The power of water: spirits and knowledge in West Java. Issue 2 (15th March 2022) - Hellman, Jörgen
ABSTRACT: This contribution explores a specific form of knowledge used by a pilgrim leader on the island of Java which constitutes the basis of his religious legitimacy and political agency. By locating the source of his knowledge in his personal relationships with the ancient kings of Pajajaran, the pilgrim leader creates a position from where he can criticise the contemporary political and religious leadership of Indonesia. He builds the authority for this position on his direct communication with the ancestors, and by demonstrating his ability to infuse various objects and material forms with powers to obscure the distinction between past and present. The pilgrim leader's knowledge facilitates access to the power of water for pilgrims in various ways. Relationships with specific ancestors are established and validated through nocturnal 'possessions' and detailed knowledge about the spiritual landscape of Sancang, including the powerful springs of Sumur Tujuh. The ethnography is based on several pilgrimages in West Java, but especially focuses on one occasion when water played a crucial role in blurring the demarcation between the living and the dead, between humans and spirits.